Clients' willingness to pay for immunization services in the urban and rural primary health centers of Enugu state, Nigeria - Edmund Ndudi Ossai; Akinola Ayoola Fatiregun (AOSIS, 2015)
Our study aims at determining the pattern of willingness of clients to pay for childhood immunization services in urban and rural primary health centers of Enugu state, Nigeria. Using a cross-sectional design, 800 clients who presented with their children/wards to receive childhood immunization services were selected at the primary health center in rural and urban local government areas of the state. The mean age was 28.9±4.5 and 26.7±5.1 years in the urban and rural areas respectively. About 54.5% of clients in the urban and 55.3% in the rural area were willing to pay for immunization services. The clients willingness to pay was influenced by: non satisfaction with immunization services, (OR=0.3, 95%CI: 0.2- 0.5), younger age, (OR=1.4, 95%CI: 1.0-2.0) marital status (OR=2.8, 95%CI: 1.2-6.5), proximity to health centers (OR=0.6, 95%CI: 0.4- 0.8), and delivering in a private health facility (OR=0.4, 95%CI: 0.1-0.9). The study suggests that the economic value that clients give to immunization services was similar in the rural and urban areas, and this could be increased by improving the level of clients' satisfaction for the services among others.